2001
DOI: 10.1002/14356007.a08_315
|View full text |Cite
|
Sign up to set email alerts
|

Laundry Detergents

Abstract: This publication is a Science for Policy report by the Joint Research Centre, the European Commission's in-house science service. It aims to provide evidence-based scientific support to the European policy-making process. The scientific output expressed does not imply a policy position of the European Commission. Neither the European Commission nor any person acting on behalf of the Commission is responsible for the use which might be made of this publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 2 publications
2
54
0
6
Order By: Relevance
“…A number of authors have indicated the key role of liquid crystalline structures in the process of stain removal [17][18][19]. It has been observed that the maximum performance efficiency of a product is achieved when staining is in direct contact with the liquid crystalline phase, but not with an ordinary micellar solution [17][18][19]. Thus, it is beneficial to carry out the washing process at such a composition of the bath and under such conditions under which mesophases form most readily.…”
Section: Introductionmentioning
confidence: 99%
“…A number of authors have indicated the key role of liquid crystalline structures in the process of stain removal [17][18][19]. It has been observed that the maximum performance efficiency of a product is achieved when staining is in direct contact with the liquid crystalline phase, but not with an ordinary micellar solution [17][18][19]. Thus, it is beneficial to carry out the washing process at such a composition of the bath and under such conditions under which mesophases form most readily.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a review of the literature data (Calero et al, ; Lai, ; Murphy, ; Ogorzałek et al, ; Smulders, ; Wasilewski et al, ; Zoller, ) and the results of viscosity measurements performed for the commercial formulations presented in an article by the main author (Ogorzałek, Ogorzalek, ) indicated that the viscosity of this type of formulations ranged from ca. 20 to ca.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a review of the literature data (Calero et al, 2010;Lai, 2006;Murphy, 2015;Ogorzałek et al, 2019;Fig. 2 Particle size distribution in 1% aqueous solutions of the transparent fabric softeners without added extract and with 0.3% of raspberry seed extracts Smulders, 2002;Wasilewski et al, 2016a;Zoller, 2008) and the results of viscosity measurements performed for the commercial formulations presented in an article by the main author (Ogorzałek, Ogorzalek, 2017) indicated that the viscosity of this type of formulations ranged from ca. 20 to ca.…”
Section: Effect Of Hydrophobic Extractmentioning
confidence: 99%
See 1 more Smart Citation
“…In the detergent industry, however, viscous concentrated formulations are often undesirable [18]. For this reason, certain viscosity-reducing agents such as salt are added to these formulations in order to be applied in fabric softener production, thus enabling the control of the mixing operation during their production and easy handling [19].…”
Section: Introductionmentioning
confidence: 99%